The Effect of Spinning Exercise on Dysmenorrhoea for Vocational Midwifery Students at The Health Polytechnic of Palangka Raya - Titik Istiningsih; Lola Meyasa (STIKES Adi Husada, 2023)
Dysmenorrhea is pain that resembles cramps in the lower abdominal area during menstruation. Symptoms of dysmenorrhea appear in the form of pain in the midline of the lower abdomen, which begins to appear several hours before or at the same time as menstrual bleeding. This research aims to determine the effect of spinning exercise on dysmenorrhea and analyze the reduction in pain symptoms for dysmenorrhea. This research used a quasi-experimental design using a pre-post-test approach in the control and intervention groups. Data was collected on 32 students, 16 respondents in the spinning and 16 respondents in the control group-intensity measurement of spinning exercise using a cycling ergometer and measuring dysmenorrhea pain using visual analogic. The results of the statistical test between the control group and the spinning group obtained p-value = 0.027 < 0.05, which shows that group with medium and heavy-intensity spinning exercise is more effective in reducing dysmenorrhea than group with light-intensity spinning exercise. Adolescents are a group that has high activity in physical exercise. This characteristic is one of the factors for using spinning exercise treatment to treat dysmenorrhea in adolescents. This intervention becomes easier for adolescents to carry out.